Enhancing Water Use Efficiency And Crop Productivity In Tomato Cultivation Through Varying Irrigation Schedules: A Study In Open Field And Polyhouse Of Assam, India. (SAARC Journal of Agriculture, 2024)
Tomatoes are a prevalent crop commonly cultivated in the Indian state of Assam. An experiment was carried out to assess the impact of varying irrigation schedules on water use efficiency for tomato cultivation within and outside polyhouses in hilly terrain. Four drip irrigation levels were tested: Treatment-1 (T-1) (50% of crop evapotranspiration, ETc), T-2 (75% of ETc), T-3 (100% of ETc), and T-4 (125% of ETc), analysing their effects on crop growth, yield, economic benefit and water use efficiency. Tomato plants (Lycopersicon esculentum) were grown in both polyhouses and open fields, with three replications per irrigation treatment. Measurements of fruit number, individual fruit length, and yield were taken at 5-day intervals. T-1 in polyhouses exhibited superior growth and the highest yield compared to other treatments, demonstrating elevated water use efficiency. This research underscores the potential of polyhouses to enhance year-round vegetable productivity and water use efficiency in North East India's hilly regions, offering solutions for agricultural water scarcity challenges.SAARC J. Agric., 22(1): 125-138 (2024)